China and India : opportunities and threats for the global software industry - McManus, John, 1955- (Chandos Asian studies series., 2007)
In the last 30 years, the world's software industry has been developing rapidly and the landscape has also been changing dramatically. It is no longer predominately controlled by the developed countries such as the United States and the United Kingdom. This book examines the competitive and strategic issues faced by China and India through a political, economic, social, technological, environmental and legal analysis. The book reviews their competitive strengths and weaknesses and the potential risks for organisations looking to expand or invest resources in these two countries. The book also looks at the market strategies of both countries in a global context and identifies the critical success factors that have enabled China and India to gain competitive advantage in their respective markets. Importantly, the book examines the threats that these two countries pose to other countries looking to expand their presence in the global software markets. This book helps practitioners and business managers who are responsible for a firm's strategy or investment resources to grasp and understand the complexities and challenges faced by those organisations looking to expand their operations in these countries. Written from a highly knowledgeable and well-respected practitioner in the field of global strategy and software engineeringDraws on the authors wide-ranging practical experience of working with some of the worlds leading global service providers on major strategy development and service provisionProvides practical guidance to real-world problems in the global software industry.